Governance and investment of public pension assets practitioners' perspectives - Rajkumar, Sudhir; Dorfman, Mark C. (World Bank, 2011)
And key messages -- Key principles of governance and investment management -- Governance of public pension assets -- Governance structures and accountabilities -- Qualification, selection, and operation of governing bodies -- Operational policies and procedures -- Managing fiscal pressures in defined-benefit schemes -- Policy responses to turbulent financial markets -- Investment of public pension assets -- Defining the investment policy framework for public pension funds -- Managing risk for different cohorts in defined-contribution schemes -- An asset-liability approach to strategic asset allocation for pension funds -- In-house investment versus outsourcing to external investment managers -- International investments and managing the resulting currency risk -- Alternative asset classes and new investment themes.